2015
DOI: 10.1007/s00101-015-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of the i-gelTM with the LMA SupremeTM in anesthetized adult patients

Abstract: No differences were found between i-gel and LMA-S regarding leak pressure in the groups of anesthetized patients undergoing laparoscopic cholecystectomy. The LMA-S was easier to insert than the i-gel (based on its better first time success rate) and this device showed better ease of drain tube insertion, although the i-gel was quicker to insert than the LMA-S. The i-gel resulted in higher sore throat scores at 2 h postoperatively and lower POPD reduction during the 2 h period studied in the recovery room was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
2
3
1
Order By: Relevance
“…Similar findings were made by Park et al and Belena et al 12,16 On contrary Ragazzi et al reported incidence of sore throat was more in SLMA group compared to I-gel. 17 Dysphagia was reported more in SLMA group (8 cases) than I-gel group (1 case) at one hour.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were made by Park et al and Belena et al 12,16 On contrary Ragazzi et al reported incidence of sore throat was more in SLMA group compared to I-gel. 17 Dysphagia was reported more in SLMA group (8 cases) than I-gel group (1 case) at one hour.…”
Section: Discussionsupporting
confidence: 87%
“…[1314] A number of randomized clinical trials and a meta-analysis also reported that OLP between i-gel™ and LMA-S™ is similar. [678915] On the contrary to our findings, Chew et al . and Ragazzi et al .…”
Section: Discussioncontrasting
confidence: 99%
“…The special anatomically shape and rigidity of LMA-S makes it a perfect device for an easy insertion, as it has been proved by several authors when comparing LMA-S to other devices, so it explains our results (14,15,17,18).…”
Section: Tablesupporting
confidence: 65%